Quantification of flavonoids in black rice by liquid chromatography- negative electrospray ionization tandem mass spectrometry - Sriseadka T. (2017)
Systematic identification and structural characterization of flavonoids and their glycosides in bran extracts of seven Thai black rice varieties were performed by sequential uses of reversed-phase HPLC with a photodiode array detector and a combined electrospray ionization tandem mass spectrometer. Eleven flavonoids were detected, and six of these were found for the first time in rice bran. These were taxifolin-7-O-glucoside, myricetin-7-O-glucoside, isorhamnetin-3-O-acetylglucoside, isorhamnetin-7-O-rutinoside, 5,6,3′,4′,5′-pentahydroxyflavone-7-O-glucoside, and 5,3′,4′,5′-tetrahydroxyflavanone-7-O-glucoside. The quantitative results revealed that different rice varieties possessed flavonoids in different concentrations. The most abundant glycoside derivative of flavonoids widely distributed among the rice varieties was monoglucoside, such as quercetin-3-O-glucoside, isorhamnetin-3-O-glucoside, and isorhamnetin-3-O- glucoside. © 2012 American Chemical Society.